Gender differences in sense of coherence among university students during the COVID-19 pandemic in Turkey - Kayi, Ilker; Uzunkoeprue, Gizem; Dadaczynski, Kevin; Soylar, Pinar; Otludil, Bugra; Duendar, Pinar; Sakarya, Sibel (Oxford Univ Press, 2023)
Non-pharmaceutical interventions (NPIs) implemented to mitigate the COVID-19 pandemic halted everyday life in higher education along with social and psychological impacts. The objective of our study was to explore the factors related to sense of coherence (SoC) from a gender perspective among university students in Turkey. This is a cross-sectional survey conducted online with a convenience sampling method as part of the international COVID-Health Literacy (COVID-HL) Consortium. SoC was measured by a nine-item questionnaire that was adapted to the Turkish language, including socio-demographic information and health status, including psychological well-being, psychosomatic complaints, and future anxiety (FA). 1595 students from four universities, of whom 72% were female, participated in the study. Cronbach's alpha for the SoC scale was 0.75. Based on the median split of the individual scores, levels of SoC showed no statistically significant difference according to gender. Logistic regression analysis indicated that higher SoC was associated with medium and high subjective social status, studying in private universities, high psychological well-being, low FA, and none/one psychosomatic complaint. While results were similar among female students, type of university and psychological well-being showed no statistically significant association with SoC among males. Our results indicate that structural (subjective social status) and contextual (type of university) factors, along with gender-based variations, are associated with SoC among university students in Turkey.
Keywords: gender; COVID-19; higher education; psychosomatic complaints; psychological well-being; sense of coherence